Describing English Restaurant Menu in Sign Language by Local Deaf and Hard of Hearing Restaurant Staff in Lovina Bali: Mendeskripsikan Menu Restoran Berbahasa Inggris dalam Bahasa Isyarat oleh Staf Restoran Tunarungu dan Tunarungu Lokal di Lovina Bali - Karisma, Made Arya Wira; Sudana, Putu Ayu Prabawati; Adnyani, Ni Luh Putu Sri (Jurnal IKA, 2025)
This study aims to describe how deaf and hard-of-hearing restaurant staff in the Lovina area of Bali explain English-language restaurant menus using local sign language when communicating with international customers. Additionally, the research explores how staff communicate about items not listed on the menu. A qualitative descriptive approach was employed, involving direct observation and in-depth interviews with deaf and hard-of-hearing staff at restaurants in Lovina The findings indicate that the staff utilize local sign language to effectively convey menu information to international customers. In instances where menu items are not available, they employ a combination of gestures, written notes, and translation applications to facilitate communication. This research highlights the importance of training in international sign language and the development of visual aids to enhance interactions between deaf and hard-of-hearing staff and international customers in the hospitality sector.